2015
DOI: 10.1007/s00217-015-2465-3
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriocin production by lactic acid bacteria isolated from fish, seafood and fish products

Abstract: suitability of fish, seafood and fish products for the isolation of LAB (mainly enterococci), including (multi)bacteriocinogenic strains, encoding bacteriocins active against Listeria monocytogenes and other food-borne pathogens of interest for the food industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 56 publications
2
20
0
4
Order By: Relevance
“…In this study, the 8 P. acidilactici strains displayed a broad antimicrobial spectrum against fish pathogens, which could be due to different antimicrobial metabolites such as organic acids (mainly lactic acid), hydrogen peroxide, diacetyl, acetaldehyde, and/or bacteriocins, with the organic acids and bacteriocins being the key weapons in inhibiting pathogens of relevance for aquaculture (Gillor et al 2008, Desriac et al 2010. In this respect, 6 out of 8 P. acidilactici strains were found to be bacteriocin producers, based on the proteinaceous nature and heat stability of the antimicrobial agent, which is in agreement with previous studies, where a remarkably high number of LAB displaying antimicrobial activity against fish pathogens were potential bacteriocin producers (Muñoz-Atienza et al 2013, Gómez-Sala et al 2015. However, the results indicated that the antimicrobial activity against L. garvieae exerted by the pediococci was not due to the production of bacteriocins, as the antimicrobial effect was only observed in the presence of pediococcal cells.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the 8 P. acidilactici strains displayed a broad antimicrobial spectrum against fish pathogens, which could be due to different antimicrobial metabolites such as organic acids (mainly lactic acid), hydrogen peroxide, diacetyl, acetaldehyde, and/or bacteriocins, with the organic acids and bacteriocins being the key weapons in inhibiting pathogens of relevance for aquaculture (Gillor et al 2008, Desriac et al 2010. In this respect, 6 out of 8 P. acidilactici strains were found to be bacteriocin producers, based on the proteinaceous nature and heat stability of the antimicrobial agent, which is in agreement with previous studies, where a remarkably high number of LAB displaying antimicrobial activity against fish pathogens were potential bacteriocin producers (Muñoz-Atienza et al 2013, Gómez-Sala et al 2015. However, the results indicated that the antimicrobial activity against L. garvieae exerted by the pediococci was not due to the production of bacteriocins, as the antimicrobial effect was only observed in the presence of pediococcal cells.…”
Section: Discussionsupporting
confidence: 89%
“…Our results are in agreement with the findings of previous studies. Gómez-Sala et al (2015) demonstrated that analysis of 1245 LAB isolates obtained from fish, seafood, and fish products showed that 197 exerted direct antimicrobial activity against 20 spoilage and food-borne pathogenic microorganisms. Furthermore, LAB isolates selected on the basis of their direct antimicrobial activity were identified as E. faecium, E. faecalis, Pediococcus pentosaceus, Weissella cibaria, L. sakei subsp.…”
Section: Resultsmentioning
confidence: 99%
“…The enterococci comprised the largest LAB group with antimicrobial activity (91 %) with E. faecium (40 %) as the most identified antagonistic species. Enterococci with antimicrobial activity have been previously identified from LAB isolated from mammals, birds and fish [ 10 12 ], but not with this elevated percentage of isolation. Enterococci are also the most common species in cloacal and pharyngeal samples of Euroasian griffon vultures [ 26 ] and in Turkey and Black vultures whereas enterococcal symbionts living in the hoopoe ( Upua epops ) uropygial gland produce bacteriocins active against Gram-positive pathogens [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Environmental sources as well as wild and game animals are a powerful source of bacteriocin-producing LAB [ 10 12 ]. Griffon vultures ( Gyps fulvus subspecies fulvus ) belong to the Old World vultures group, a diverse mix of colonial cliff-nesting scavenger birds that play an essential ecological role as garbage collectors and recyclers.…”
Section: Introductionmentioning
confidence: 99%